2022
DOI: 10.1186/s12933-022-01547-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose dysregulation and subclinical cardiac dysfunction in older adults: The Cardiovascular Health Study

Abstract: Objective We evaluated whether measures of glucose dysregulation are associated with subclinical cardiac dysfunction, as assessed by speckle-tracking echocardiography, in an older population. Methods Participants were men and women in the Cardiovascular Health Study, age 65+ years and without coronary heart disease, atrial fibrillation, or heart failure at baseline. We evaluated fasting insulin resistance (IR) with the homeostatic model of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, our study was the first to use strain analyses derived from MRI feature tracking to explore the effect of insulin use on changes in LV mechanics. In a CHS cohort study, Garg et al observed that higher insulin secretion was associated with worse LV longitudinal systolic function in an older population with prediabetes and diabetes [ 19 ]. In contrast, with regard to HFrEF comorbid with T2DM, data from this study displayed worse longitudinal and circumferential systolic strain values in individuals on insulin than in those not on insulin.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study was the first to use strain analyses derived from MRI feature tracking to explore the effect of insulin use on changes in LV mechanics. In a CHS cohort study, Garg et al observed that higher insulin secretion was associated with worse LV longitudinal systolic function in an older population with prediabetes and diabetes [ 19 ]. In contrast, with regard to HFrEF comorbid with T2DM, data from this study displayed worse longitudinal and circumferential systolic strain values in individuals on insulin than in those not on insulin.…”
Section: Discussionmentioning
confidence: 99%